Program Kerja Humas PT. SBA Pada Masa Pandemi Covid-19 - Romi Saputra; Salman Alfarisi (Sadida Islamic Communications and Media Studies, 2021)
PT. SBA lhoknga is a company that produces cement located in Lhoknga, Aceh Besar. A company should have public relations or public relations in running a company. This is because companies cannot be separated from society. Public trust is very influential for the company because it will have an impact on the sales of the company's products. These programs are expected to grow and increase public trust. Public relations members are required to think more creatively in carrying out their duties, even more so during this pandemic